Women’s Representation in Political Parties as an Effort to Achieve Gender Equality - Radhiyah Rahma; Regina Aprillia; Moch. Ali Mashuri (SWATANTRA, 2024)
Indonesia is a large archipelagic country. As the largest archipelagic state in the world, Indonesia is characterised by considerable diversity in terms of geographical location, population, culture, and politics. This diversity has shaped Indonesia into a democratic state, which upholds the principle of government of the people, by the people, and for the people. From this principle, it can be inferred that governmental actions in Indonesia originate from the people and are intended for the people. Equal rights to participate in governing the country are formally recognised within Indonesia’s political system. However, in practice, political life in Indonesia still reflects gender-based discrimination. Law Number 2 of 2008 on Political Parties and Law Number 10 of 2008 mandate the importance of political education that takes justice and gender equality into account. The purpose of this study is to analyse and examine women’s representation in political parties as an effort to promote gender equality. The study employs a qualitative research method, using a literature review as the data collection technique, while the data are analysed through data presentation and conclusion drawing. The research was conducted at the Regional People’s Representative Council of East Java Province. The findings indicate that women’s participation in politics today tends to be more positive. Nevertheless, the increasing number of female legislative members from one period to another has not yet been able to free women from the gender inequality they continue to experience.